The Impact of Digital Technologies on Public Health in Developed and Developing Countries 18th International Conference, ICOST 2020, Hammamet, Tunisia, June 24-26, 2020, Proceedings - Jmaiel, Mohamed; Mokhtari, Mounir; Abdulrazak, Bessam; Aloulou, Hamdi; Kallel, Slim (Information Systems and Applications, incl. Internet/Web, and HCI, 2020)
This open access book constitutes the refereed proceedings of the 18th International Conference on String Processing and Information Retrieval, ICOST 2020, held in Hammamet, Tunisia, in June 2020.* The 17 full papers and 23 short papers presented in this volume were carefully reviewed and selected from 49 submissions. They cover topics such as: IoT and AI solutions for e-health; biomedical and health informatics; behavior and activity monitoring; behavior and activity monitoring; and wellbeing technology. *This conference was held virtually due to the COVID-19 pandemic.